Critical social theory and geography: observations on the critical of everyday life - Queiroz, Rodrigo José de Góis (Geografares, 2020)
The begining of critical geography in the last quarter of the 20th century increased the space in a critical social theory, the space role for social transformation and the spatial turning in the human science. In this context, through extensive bibliographic research, we propose a reflection based in Lefebvre and the Situationists about critical of everyday life to an approximation with sociospatial reality.